Efficacy of denture cleansers on Candida albicans adhesion and their effects on the properties of conventional, milled CAD/CAM, and 3D-printed denture bases - Bento, Victor Augusto Alves [UNESP]; Sayeg, João Mateus Cavalaro [UNESP]; Rosa, Cleber Davi Del Rei Daltro [UNESP]; Lopes, Leonardo Ferreira de Toledo Piza [UNESP]; Marques, Maria Carolina Silva; Pellizzer, Eduardo Piza [UNESP] (Springer Nature, 2024)
Objectives: Evaluate the efficacy of denture cleaners on the adhesion of Candida albicans and their effects on the surface, optical, and mechanical properties of resins for conventional, milled, and 3D-printed denture bases. Materials and methods: A total of 240 resin samples were made, 120 for testing Candida albicans adhesion, optical stabilities (ΔE00), roughness (Ra), hydrophilicity (°), surface free energy (Owens-Wendt) and 120 samples for testing Candida albicans adhesion, surface microhardness (Knoop), flexural strength and modulus of elasticity in a three-point test, in which they were divided into 3 groups of denture resin (n = 40) and subdivided into 5 cleaners of dentures (n = 8). Data were evaluated by two-way ANOVA and Tukey’s test for multiple comparisons (α = 0.05). Results: Denture cleaners with an alkaline solution and dilute acid composition were those that showed the greatest effectiveness in reducing Candida albicans (P < 0.001), however 1% NaOCl significantly affected the properties of the resins (P < 0.05). Denture 3D-printed showed that the surface microhardness was significantly lower for all cleansers (P < 0.05). Conclusions: Listerine demonstrated superior efficacy in reducing Candida albicans with minimal effect on denture properties, whereas 1% NaOCl had a significant negative impact on the properties. The mechanical properties were significantly lower in 3D-printed resin than in other resins for all denture cleansers. Clinical relevance: Denture base materials are being sold to adapt to the CAD/CAM system, increasing the number of users of dentures manufactured with this system. Despite this, there is little investigation into denture cleaners regarding the adhesion capacity of microorganisms and the optical, surface and mechanical properties of dentures, thus requiring further investigation.
Keywords: CAD/CAM; Candida albicans; Denture; Disinfection; Material science